Three essays on agricultural household labor in developing countries - Munsu, Kang (Kansas State University, 2020)
Agricultural labor supply in developing countries is an important factor in agricultural productivity and livelihood. Labor productivity, however, is still inefficient due to both internal and external factors. In particular, land markets, credit markets, and social networks are crucial for improving household labor allocation efficiency and, accordingly, agricultural productivity. This dissertation examines the role of gendered land ownership and microcredit on intra- and inter-household labor allocation in Sub-Saharan Africa. Recent research has increased interest in the intersection of land tenure and gender roles in African agriculture. While formalization of land ownership has been found to have significant impacts in terms of gender, time-use and management remain critical to both the productivity of agricultural operations and the welfare of household members. Thus, it is important to understand how gender intersects with the relationships between the ownership and operation of plots. To address these relationships, in Chapter 1, we used plot-level data from nationally representative household surveys in Ethiopia and Malawi to characterize the ownership structure (e.g., sole male, sole female, or joint) and domain (e.g., plot ownership, plot management, or output management) of control over land in each household. We then answered the following research questions: 1) Are there any gender gaps in the degrees of the concordance among different domains of controls? 2) How does the structure of ownership and managerial rights affect labor allocations on plots? We found that for both males and females, sole managerial rights are most likely to occur in plots owned exclusively by either gender. However, on jointly owned plots, instances of sole planting rights are almost exclusively male. We also found that while females supply more of their own labor on plots they control, the pattern of own-gender bias in labor allocation varies with each structure-domain combination. The heterogeneity of these results suggests gender inequality analyses related to land rights are sensitive to the choice of domain of control. Chapters 2 and 3 explores the microcredit impacts on inter-household labor sharing in developing countries. Labor sharing in developing countries is related to liquidity constraints, labor deficiency, and seasonality problems. Recent credit policies for the poor in developing countries have significantly increased household livelihood, but there is still ambiguity regarding liquidity effects on shared labor supply. Our research questions were: 1) Does microcredit impact labor sharing arrangements in rural economies? 2) What is the role of network effects on labor sharing groups? We examined these questions both theoretically and empirically. The theoretical section of Chapter 2 develops a two-period model which includes liquidity constraints. The results of this section show that as the size of the microcredit loan increases, labor sharing and input expenditure also increase. However, family labor supply changes depend on households’ preferences regarding leisure, and network effects reduce the effects of microcredit on labor supply and input expenditure. Households with high network effects are less likely to change their shared labor allocation in response to access to larger loans. In Chapter 3, we used panel data from the Ethiopian Rural Household Survey collected during 1999 to 2009 to answer the above research questions. Three different types of credit services were included in the household fixed effect model as covariates to examine their impact on household labor supply changes over the years. We found that shared labor supply and family labor supply do not change with microcredit loan benefits. These results suggest that liquidity is not the primary reason for households to supply shared labor. Our results are more consistent with Gilligan (2004) and Mekonnen and Dorfman (2017), who showed that network synergies exist in labor sharing groups. Microcredit loan-takers also purchase more fertilizer, and the effects of microcredit loans on fertilizer expenditure are similar to the effects of fertilizer credit programs. The effects of other credit services on household labor supply are heterogeneous. Village network loan-takers allocate more labor days in labor sharing networks. One possible reason for this is that households are motivated to supply labor in labor sharing networks if they receive credit services from the network. Our results also suggest that social ties and peer pressure encourage network loan-takers to participate in labor sharing groups, whereas fertilizer credit program participants supply less labor in labor sharing networks.
Keywords: Household labor; Sub-Saharan Africa; Gender; Microcredit